Analysis of PGSD students' perception of the implementation of STEAM in learning literacy and numeracy - Elok Fariha Sari; Yl Sukestiyarno; Wiwi Isnaeni; Sarwi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The STEAM approach is closely related to 21st-century skills that accommodate innovation in thinking and skills so as to create superior learning outcomes. This study aims to present the results of a descriptive survey on the application of STEAM in numeracy literacy learning in PGSD students. The method in this study uses a quantitative descriptive method supported by a survey through a questionnaire on Google Form and a WhatsApp Group. The subjects of this study are 81 PGSD students. The results of the study showed a significant gap in students' perceptions of STEAM implementation, namely that 55.6% of students already understood the STEAM approach; on the other hand, only 34.6% of students in the category agreed to integrate numeracy concepts with STEAM components. Meanwhile, 66.3% of students believe that STEAM can help students develop problem-solving skills in numeracy. It is necessary to strengthen STEAM-based learning to encourage numeracy literacy skills.